Impregnação supercrítica de carotenoides da torta do mesocarpo do dendê (elaeis guineensis) na farinha de mandioca (manihot esculenta crantz) - TUPINAMBÁ, Renan Araújo Siqueira (Universidade Federal do Pará, 2023)
Brazil is the second largest producer of manioc (Manihot esculenta Crantz), with an average production of 24.6 million. This tuber is an important source of carbohydrates, being used mainly in the production of flour for human consumption. In view of this, this work investigated the enrichment capacity of manioc flour with carotenoids of palm mesocarp pie, transforming it into functional food by the use of supercritical CO2 as transfer fluid in the extraction/impregnation process. The impregnation of carotenoids from palm mesocarp cake in cassava flour was carried out using a supercritical extraction plant installed in the Laboratory of Separation Operations, located at the Federal University of Pará. The lipid content found in the palm mesocarp pie is still Considerable, about 12.83%, and this contains a carotenoid concentration of 5070.54 μg/g. The time of impregnation was the variable that showed the greatest significant difference between applied experiments, where at a time of 20 minutes the cassava flour presented more satisfactory results as the concentration of impregnated β- carotene. The impregnated oil mass and water activity of the final product were satisfactory, as the flour presented a pleasant physical appearance, as well as it’s water activity levels remained within the ideal range for the flour stability, with lower water activity values to 0.6. In this way, the enriched flour presented high capacity of impregnation of carotenoids using supercritical fluid, corroborating the fact that β-carotene presents as an excellent natural dye.